(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The integration of Radio Frequency Identification (RFID) and telecommunication technologies in supply chain management (SCM) has become increasingly critical in enhancing the efficiency and transparency of operations within the food industry. This paper explores the application of RFID and telecommunication systems to address the complexities of food supply chains, characterized by perishable goods, strict regulatory requirements, and the need for traceability. The adoption of RFID technology facilitates real-time tracking of products, from farm to fork, enabling stakeholders to monitor the movement, storage conditions, and inventory levels with precision. Concurrently, telecommunication networks play a pivotal role in ensuring seamless data exchange across geographically dispersed locations, thus enhancing communication between suppliers, distributors, and retailers. This research highlights the synergistic potential of combining RFID with telecommunication to optimize key supply chain processes, such as inventory management, demand forecasting, and quality control. By enabling real-time data collection and sharing, this integration significantly reduces the likelihood of stockouts, overstocking, and food spoilage, which are critical concerns in the food industry. Furthermore, the study underscores the role of these technologies in ensuring food safety and compliance with regulatory standards through improved traceability and rapid response to recalls. Through case studies and empirical analysis, the paper demonstrates the operational benefits and challenges associated with implementing RFID and telecommunication in food supply chains. The findings suggest that while the integration of these technologies offers substantial gains in efficiency, cost savings, and customer satisfaction, it also requires careful planning and investment in infrastructure. This study provides valuable insights for industry practitioners and policymakers aiming to enhance the resilience and sustainability of food supply chains through technological innovation.